Development of rice field and mangrove tourism center for conservation and edu-ecotourism in Bukit Terap Village - Aqsal Fizizka; Yulius Bimantaka; Syawaludin Djailani; Indriyani Indriyani; Sri Okta Viana Hatibie; Radhiatunisa Radhiatunisa; Dilla Asrizalni; Anisa Maharani; Irdayanti Irdayanti; Hevitria Hevitria (Universitas Muhammadiyah Magelang, 2024)
The design stems from the insufficient public attention towards the tourism potential in Bukit Terap village, resulting in minimal tourist interest in visiting the area. To bolster the community's economy, there's a need to conserve natural resources, which is expected to enhance the tourism sector. The objective of this initiative is to offer alternative solutions by developing rice field and mangrove concepts for natural resource conservation and edu-ecotourism, tailored to the geographical landscape of Bukit Terap village. This involves activities such as conceptual design and raising awareness about the importance of conserving natural resources as a tourist attraction. As a result, a master plan for ecotourism development in Bukit Terap Village has been formulated and agreed upon by the community.